Sarcopenia and health-related outcomes: an umbrella review of observational studies - Veronese, Nicola; Demurtas, Jacopo; Soysal, Pinar; Smith, Lee; Torbahn, Gabriel; Schöne, Daniel; Schwingshackl, Lukas; Sieber, Cornel; Bauer, Jurgen; Cesari, Matteo; Bruyere, Oliviere; Reginster, Jean Yves; et al. (European Geriatric Medicine, 2019)
Background The clinical relevance of sarcopenia has increasingly been recognized. However, whether it is associated with the development of other medical conditions is still unclear. Therefore, we aimed to capture the scale of outcomes that have been associated with the presence of sarcopenia and systematically assess the quality, strength, and credibility of these associations using an umbrella review methodology. Methods A systematic review in several databases was carried out, until 20th February 2019. For each association, random-effects summary effect size, 95% confidence intervals (CIs), heterogeneity (I2), evidence for small-study effect, evidence for excess significance bias, and 95%-prediction intervals were estimated. We used these metrics to categorize the evidence of significant outcomes (p < 0.05) from class I (convincing) to class IV (weak), according to pre-established criteria. Results From 358 abstracts, 6 meta-analyses with 14 associations were included. Sarcopenia was associated with higher risk of other comorbidities and mortality in 11 of 14 outcomes explored. However, only 3 outcomes (i.e., association between sarcopenia and increased risk of death in community-dwelling older people [odds ratio, OR = 3.60; 95% CI 2.96–4.37; n = 14,305], disability [OR = 3.04; 95% CI 1.80–5.12; n = 8569], and falls [OR = 1.60; 95% CI 1.31–1.97; n = 12,261]) presented a highly suggestive evidence (class II). Other association was classified as having only a weak evidence. Conclusion Sarcopenia is associated with several adverse health-related outcomes in older people, and its associations with mortality, disability, and falls are supported by a highly suggestive evidence. The effect of interventions on sarcopenia to improve these outcomes needs to be investigated.
Keywords: Sarcopenia; Health; Umbrella review; Meta-analysis; Mortality; Fall; Disability; Risk factor